Black to the Future: Traversing Digital Time and Space Toward a Critical Race Technomethodology - Brown, Taryrn T C; Phelps-Ward, Robin; Smith, Travis C; Stewart, Terah J; Breeden, Roshaunda L; McGowan, Brian L (Departures in critical qualitative research, 2025)
Envisioning a more empowered and liberated future for Black people, this article speaks to the ability and capacity of Black digital practice in visual methodologies and research. New approaches in critical qualitative methods, which demand many skills and abilities by researchers, continue to evolve amid the ever-evolving media technologies that are an integral part of and even inherent in our day-to-day lives. In the age of technological innovation and possibility, the methodological imagination propels forward, prompting space to consider how we might consider and build toward new and diverse forms of media and technology that permeate our multiliteracies (Lewis Ellison, 2023; Price-Dennis, 2016; Sealey-Ruiz, 2019). Acknowledging the need for more Black-centered methodological analysis (McClish & Bhattacharya, 2024) and witnessing the evolution of a global media culture, this article seeks to reckon with the growing impacts of technologies that leverage, socialize, and impact identity and its translation into the research space through methodology.Utilizing contributions from Afrofuturism (Womack, 2013), digital Black feminisms (Steele, 2021), and Black cybercultures (Bailey, 2021; Brock, 2020b), this article highlights the cartographies of Black cultural digital practice and methods to critically examine the ubiquity of anti-Black racism within socio-technical architectures (e.g., code, data, algorithms, and interfaces). Through a systematic review of the literature, the article aims to acknowledge the scholarly negotiations of new media technologies toward findings that evoke heightened critical consciousness that impacts both physical and digital contexts for algorithmically and racially just counter-technologies. In this review of the literature and the organizing of thematic similarities of these approaches to critical qualitative research, this article also proposes the conceptualization of a critical race technomethodology that bridges the scholarship across disciplines that upholds the power of digital space and methodology as a new departure in critical qualitative research.